Living with air plants : a beginner's guide to growing and displaying Tillandsia - Lesseig, Ryan; Matsuda, Yukihiro (Tuttle Publishing, 2018)
Living with Air Plants is the perfect introduction to the world of Tillandsia and the many ways they can be used to design and upgrade your home or work space. It is the work of a prominent horticulturist and a design, lifestyle and gardening expert from Japan, and displays a wonderful Japanese design aesthetic and attention to detail. These endearing plants are friendly to seasoned gardeners and beginners alike, and easy to grow and care for, once you know how. This reference and growing guide covers over 100 different Tillandsia varieties, and gives you all the information you need to select your plants and make them thrive.